Land Use Projection for Spatial Plan Consistency in Jabodetabek - Diyah Novita Kurnianti; Ernan Rustiadi; Dwi Putro Tejo Baskoro (Faculty of Geography, Universitas Gadjah Mada, 2015)
Land use changes in Greater Jakarta area are very dynamic because of the need for settlements and converting agricultural land. It indicates land use inconsistency regard to spatial plan that can cause land damage in the future. Land use which has potential inconsistency in the future are requires for land use control in this region. This study uses spatial analysis to look at the potential inconsistencies by comparing land use projection in the future in two scenarios that is with and without control by policies. Policies in this study are land suitability and forest allocation. The result shows that land use consistency with policies raise until 97,4 % but only 93.9 % without control by policies. Areas that could potentially have inconsistency in the future are Bogor, Bekasi, Tangerang and Jakarta North City for area which is directed as forest and buffer zones of cultivation.